Warthins Tumour in Accessory Parotid Gland (Bangladesh Journal of Otorhinolaryngology, 2015)
The accessory parotid gland is salivary tissue separated from the main parotid gland and lying on masseter muscle. The accessory parotid gland is not rare, according to cadaver studies, but neoplasm in the accessory parotid gland is rare. Surgical excision is the treatment of choice for the accessory parotid gland tumour. It is important to identify the buccal branch of the facial nerve to avoid injury to the facial nerve. Herein we describe a case of accessory parotid gland tumor in a 30 years old lady. Histopathological diagnosis was Warthins tumour which is very rare in female. DOI: http://dx.doi.org/10.3329/bjo.v20i1.22017 Bangladesh J Otorhinolaryngol; April 2014; 20(1): 43-45